Ewolucja podejścia do partycypacji pracowniczej w koncepcjach zarządzania ludźmi - Cierniak-Emerych, Anna (Evolution in the Approach to Employee Participation in Concepts of Human Resources Management, 2009)
The aim of the paper is presenting the changes in employee participation in concepts of human resources management, undergoing transformation throughout the years. Assuming that these transformations are processes, the author referred to the traditional concept of Personnel Management, the modern Human Resources Management, as well as the increasingly popular collection of concepts High Performance Work Systems (HPWS) and the trend of High Involvement Work Practices (HIWP). Bearing this in mind, the last part of the paper describes the - identified in Polish based companies -barriers in participation, showing ways of overcoming them. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 34-40